Australian family carer responses when a loved one receives a diagnosis of Motor Neurone Disease—“Our life has changed forever” - O'Connor, M.; Aoun, Samar; Breen, Lauren (Wiley-Blackwell Publishing Ltd., 2018)
While the experiences of family members supporting a person with a terminal illness are well documented, less is known about the needs of carers of people with neurological diseases, in particular, Motor Neurone Disease (MND). This paper describes the qualitative data from a large Australian survey of family carers of people with MND, to ascertain their experiences of receiving the diagnosis. The aim of the study was to describe the experiences of family carers of people with MND in receiving the diagnosis in order to inform and improve ways in which the diagnosis is communicated. Anonymous postal surveys were sent to people with MND in Australia and their family carers respectively. The perceived ability/skills of neurologists was assessed using a five‐point scale from excellent to poor. Attributes of communication of bad news was measured by the SPIKES protocol. Each survey question invited further written responses. Eight hundred and sixty‐four questionnaires were posted to people with MND and their family carers, with assistance from MND associations. One hundred and ninety‐six family carers submitted responses, of which 171 (88%) were patient‐carer dyads. Analyses were conducted on 190 family carers. Five themes emerged from reading and re‐reading written responses: frustrations with the diagnosis; giving information; family carer observations of the neurologist; the setting; and what would have made the diagnosis easier? The delivery of the diagnosis is a pivotal event in the MND trajectory. Satisfaction for patients and their family carers is related to the neurologists showing empathy and responding appropriately to their emotions, exhibiting knowledge and providing longer consultations. Neurologists may benefit from education and training in communication skills to adequately respond to patients’ and families’ emotions and development of best practice protocols.